35.6k views
2 votes
How to do 28a ? Thanks

How to do 28a ? Thanks-example-1
User Techmad
by
4.8k points

2 Answers

1 vote

Answer:

Explanation:

(m+1)²+(m-1)²=m²+2m+1+m²-2m+1=2m²+2=2(m²+1)

User Yasin Mushtaq
by
5.0k points
3 votes

Answer:

True it does.

Explanation:

(M+1)^2 + (M-1)^2 = 2(m^2 + 1)

M^2 + 2m + 1 + m^2 - 2m + 1 = 2(m^2 +1)

2m^2 + 1 = 2(m^2 + 1)

There's your work.

The ^ means number after is exponent.

Hope this helps, and have a good day :)!

User MLN
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.